Performance-Based Durability Assessment of Low Carbon Concrete Using Electrical Resistivity - Jaehwan Kim; Ki-Tae Park; Jinyoung Yoon (International Journal of Concrete Structures and Materials)
Abstract A performance-based approach is essential for evaluating the long-term durability and performance of concrete. Nondestructive methods, such as electrical resistivity measurements, offer significant advantages in this context due to their simplicity, speed, and cost-effectiveness. This study applied electrical resistivity as a tool to assess key performance factors, including compressive strength and chloride transport properties, in concrete mixtures with and without supplementary cementitious materials (SCMs). The results demonstrated strong correlations between electrical resistivity and the performance factors across all concrete mixtures, highlighting its potential as a reliable evaluation method. While electrical resistivity shows promise for quantifying performance factors, challenges remain in addressing variability and measurement accuracy. Further investigations are recommended to refine the method and enhance its applicability in practical durability assessments.